1997
DOI: 10.1162/neco.1997.9.1.77
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Neural Network Exhibiting Selective Activation of Neuronal Ensembles: From Winner-Take-All to Winners-Share-All

Abstract: A neuroecological equation of the Lotka-Volterra type for mean firing rate is derived from the conventional membrane dynamics of a neural network with lateral inhibition and self-inhibition. Neural selection mechanisms employed by the competitive neural network receiving external inputs are studied with analytic and numerical calculations. A remarkable findings is that the strength of lateral inhibition relative to that of self-inhibition is crucial for determining the steady states of the network among three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 19 publications
5
116
0
Order By: Relevance
“…In simulation, they have shown that winner-takes-all like competition occurs within a single domain, while winners-share-all dynamics (multiple active neurons) occur in networks composed of multiple overlapping domains (Wickens et al, 1991;Alexander & Wickens, 1993). Similar results have been obtained in analytical studies of general mutually inhibitory neural networks (Fukai & Tanaka, 1997).…”
Section: Introductionsupporting
confidence: 66%
“…In simulation, they have shown that winner-takes-all like competition occurs within a single domain, while winners-share-all dynamics (multiple active neurons) occur in networks composed of multiple overlapping domains (Wickens et al, 1991;Alexander & Wickens, 1993). Similar results have been obtained in analytical studies of general mutually inhibitory neural networks (Fukai & Tanaka, 1997).…”
Section: Introductionsupporting
confidence: 66%
“…A second class of distributed selection architectures is illustrated by the network shown in Figure 3B. In architectures of this type all competitors are reciprocally connected so that each one has an inhibitory link to every otherÑan arrangement termed recurrent reciprocal inhibition 27,94 Ñand an excitatory link to the shared output resource. Such networks display a form of positive feedback since increased activity in one competitor causes increased inhibition on all others thereby reducing their inhibitory effect on the first.…”
Section: Selection Architecturesmentioning
confidence: 99%
“…At the same time, non-winning neurons become silent due to the dynamics of the neurons in the network, not because they are algorithmically reset. Previous seminal works also studied the neural dynamics leading to emergent competition in terms of the different properties potentially involved in the process, like the strength and range of lateral inhibition [9][10][11], the value of the firing threshold [10,18] and the steepness of the activation function [18].…”
Section: Introductionmentioning
confidence: 99%